Forensic enhancement of shoe print images using adobe® photoshop® - Sarifudin, Sarah Aliah Amir (Universiti Sains Malaysia, 2015)
Recovery of shoe prints at crime scenes provides useful information in investigation and act as valuable evidence of the crime. Unfortunately, most shoe print evidence are placed aside due to the poor state of the evidence, absence of comparison samples, and the lacking of knowledge and exposure towards such evidence. Many recovered shoe prints at crime scenes are in low quality which contribute in the difficulties of identification and comparison processes. Preservation and digital forensic enhancement of shoe print images are essential in providing an increase of the evidential value of such prints. The study builds on the utilisation of commercially available image processing software Adobe® Photoshop® CC for the forensic enhancement of shoe print images. Several shoe print images made on different surfaces i.e. newspaper, rubber mat and carpets; were photographed using a Canon EOS 40D Digital Single Lens Reflect (DSLR) camera. These shoe prints were created using black ink stamp pad. The enhancement of the shoe print images were performed using the Adobe® Photoshop® CC adjustment and filter tools which include white balance, colour adjustment, and sharpen filters. The shoe print images were successfully enhanced by either fully or partial reduction of the noise background to contrast the prints from their backgrounds. The isolation of the shoe prints from the backgrounds has improved the clarity of the shoe prints and therefore aid in further comparison and identification analysis.